Information technologies as an integral part of the process of physical education of student youth - Igor Vypasniak; Andriy Shankovsky (Kazimierz Wielki University, 2017)
Topicality. The process of modernizing the professional training of specialists in the sphere of physical culture and sports fits into the present general strategy of educational policy of Ukraine, the primary task of which is to achieve the modern quality of education, its conformity to current perspective needs of the individual, society and the state. Objectives of the Research: to analyze and systematize modern scientific and methodological knowledge and the results of practical experience of domestic and foreign researchers in the sphere of the use of information technologies in the practice of physical education of students; to develop informational and methodical multimedia system "Рerfectum Corpus", as a means of raising the level of theoretical knowledge of students in the process of physical education. Research results. The functioning of the information environment of the higher educational establishment envisages the widest possible use of computer technology, multimedia technologies, local computer networks during the transfer of the student's material, as well as in the system of monitoring the quality of the formed knowledge and during self-training with the help of the global Internet network. The strategy of integrating IT into the process of physical education, in our opinion, should be aimed at: the formation of values of a healthy lifestyle and creativity; the formation of value attitude of young people to their own health, the improvement of physical preparedness taking into account requirements of future professional activity; the formation of an active personal position in achieving harmonious development; the use of healthy technologies in the pedagogical process; the restructuring of leisure with the use of fitness and various types of recreational motor activity; supporting students' interest in improving motor activity. Conclusions. The multimedia informational and methodical system "Perfectum Corpus" has been developed as an auxiliary training tool for the use in class and in the extracurricular activities, which is intended for self-study and raising the level of theoretical knowledge, motivation of students to exercise.